اثر الهيكل التنظيمي على الأداء في المنظمة دراسة حالة شركة سكر كنانة - د. الهادي سليمان (White Nile Journal for Studies and Research, 2017)
The study dealt with the impact of organizational climate on performance in the organization. The case study of Kanana Sugar Company Limited was aimed at identifying the dimensions of the organizational climate and the reality of the job performance in the company. The problem of the study was to answer the question: Study on descriptive analytical methodology and the most important findings of the study that the organizational structure located in the Kenana Sugar Company is suitable and the technology in the company is easy to understand and use for the employees and also found that all the existing work Kenana Sugar Company is not accomplished using technology. The most important recommendation of the study is that the management of the company should give particular attention to all elements of the organizational climate as an important variable that contributes to the impact on the job performance of the employees and enhance the sense of justice in all matters that are done among the employees of promotions, incentives, rewards and others. And the need for the participation of workers in the development of performance standards related to their functions, as well as their participation in the process of evaluating their performance and the need to improv e the physical environment of work, through the decor and office furniture and ventilation, lighting, and ease of movement better to provide psychological and physical comfort and focus on the efficiency of communications and the use of Modern Technology i n Kenana Sugar Company.